Linear accelerator-based single-fraction stereotactic body radiotherapy for symptomatic vertebral body hemangiomas: The Mayo Clinic experience. (October 2020) - Yu, Nathan Y.; Sio, Terence T.; Lyons, Mark K.; Vora, Sujay A.; Turkmani, Ali; Brown, Paul D.; Park, Sean S.; Leenstra, James L.; Bendok, Bernard R.; Schild, Steven E.; Ashman, Jonathan B.
Highlights: We report the outcome of single-fraction SBRT for symptomatic SVHs. The median SBRT dose was 18 Gy (range, 13–20). Following SBRT, 4 (67%) patients' symptoms improved and 2 (33%) were refractory. No acute or chronic toxicities associated with SBRT. SBRT is a non-invasive treatment for symptomatic SVHs. Abstract: Symptomatic vertebral hemangiomas (SVHs) are rare benign tumors that when symptomatic require procedural intervention or radiotherapy (RT). Although conventionally-fractionated RT has been an alternative to surgical resection, there is very little data on stereotactic body radiotherapy (SBRT) for SVHs. Six consecutively treated patients with SVHs underwent definitive single-fraction SBRT from 2010 to 2018 at our institution. The RT planning parameters, treatment, outcome, and toxicities are reported for 6 patients with 6 total SVHs treated with single-fraction SBRT. Each patient presented with back pain and received single-fraction SBRT to a thoracic vertebral body hemangioma. One patient had received radiofrequency ablation prior to SBRT. The median SBRT dose was 18 Gy (range, 13–20). Following SBRT, 4 (67%) patients reported improvement in presenting symptoms and 2 patients (33%) were refractory. There were no acute or chronic toxicities associated with SBRT including esophagitis, vertebral compression fractures, or myelopathy. To date, this is the largest series of single-fraction SBRT for SVHs. Single fraction SBRT appears to be a feasible option for SVHs. Further studies are needed to confirm our preliminary findings and optimize dose fractionation.